Răspuns :
a-b=12⇒a=b+12
2×a+3×b=89
2×(b+12)+3×b=89
2×b+24+3×b=89
5×b+24=89
5×b=89-24
5×b=65
b=65÷5
b=13⇒a=13+12=25
2×a+3×b=89
2×(b+12)+3×b=89
2×b+24+3×b=89
5×b+24=89
5×b=89-24
5×b=65
b=65÷5
b=13⇒a=13+12=25
sistem de a-b=12 din amandoua rezulta : system a-b=12/ori 3 rezulta :system :
2a+3b=89 2a+3b=89
system : 3a-3b=36
2a+3b=89
--------------------
5a/=125
a=25
25-b=12
-b=12-25
- b=-13/(-1)
b=13
2a+3b=89 2a+3b=89
system : 3a-3b=36
2a+3b=89
--------------------
5a/=125
a=25
25-b=12
-b=12-25
- b=-13/(-1)
b=13